Utilization of desugarized sugar beet molasses for the production of poly(3-hydroxybutyrate) by halophilic Bacillus megaterium uyuni S29. (November 2019) - Schmid, Maximilian T.; Song, Hyunjeong; Raschbauer, Michaela; Emerstorfer, Florian; Omann, Markus; Stelzer, Franz; Neureiter, Markus
Graphical abstract: Highlights: Cost effective production of poly(3-hydroxybutyrate) (P(3HB)). Bacillus megaterium uyuni S29 produces 60 g P(3HB) per 100 g cell dry mass. Desugarized beet molasses is an inexpensive substrate for P(3HB) production. Simple and robust process for (P(3HB)) production. P(3HB) polymer consisting of two fractions with a molecular mass of 722 and 189 kDa. Abstract: Desugarized sugar beet molasses is a high-salinity side stream after fractionation of beet molasses by chromatography. It could be demonstrated that this by-product of the sugar industry is a suitable substrate for the production of poly(3-hydroxybutyrate) with the halophilic bacterium Bacillus megaterium uyuni S29. Cell dry mass concentrations of up to 16.7 g L −1 with a P(3HB) content of 0.6 g g −1 were achieved after only 24 h of batch cultivation. Utilization of a desugarized sugar beet molasses medium resulted in a two- to threefold increase in biomass production compared to a conventional mineral based medium. Depending on the extraction method, the molecular mass (Mn ) of the P(3HB) varied between 119 kDa and 722 kDa. The high P(3HB) productivity of 0.42 g L −1 h −1 during batch experiments combined with desugarized sugar beet molasses as inexpensive substrate suggests a simple and robust process for cost effective P(3HB) production.